Intrapleural Administration With Rh-Endostatin and Chemical Irritants in the Control of Malignant Pleural Effusion: A Systematic Review and Meta-Analysis - Wang, Cheng-Qiong; Huang, Xiao-Rong; He, Min; Zheng, Xiao-Tian; Jiang, Hong; Chen, Qian; Fan, Teng-Yan; Zhan, Lin; Ling, Juan; Feng, Ji-Hong; Xiao, Xue; Chen, Xiao-Fan; et al. (Frontiers in Oncology, 2021)
Introduction: A modified and recombinant human endostatin (Rh-endostatin) is often used in the control of malignant pleural effusion (MPE) through intrapleural infusion. Objectives: To demonstrate the clinical response, survival and safety of Rh-endostatin plus chemical irritants, their optimal combinations, treatment threshold and optimal usage, we performed a new systematic review and meta-analysis. Methodology: All randomized controlled trials (RCTs) were collected from Chinese and English electronic databases (from inception until August 2020). We pooled the data using a series of meta-analyses, and summarized the evidence quality following the Grading of Recommendation Assessment, Development and Evaluation (GRADE) approach. Results: We included 75 RCTs recruiting 4678 patients, which reported six combinations for Rh-endostatin plus chemical irritants. All six combinations, only Rh-endostatin plus Cisplatin with enough trials might improve the complete response [2.29 (1.93, 2.71)] and quality of life [3.01 (2.49, 3.63)] and reduce the treatment failure [0.29 (0.25, 0.33)] and progressive disease [0.27 (0.22, 0.34)]. It might not increase the risk of adverse drug reactions. For patients with lung cancer, moderate to massive effusion, initial treatment, KPS score (≥ 60), or anticipated survival time (≥ 3 months), Rh-Endostatin (30 to 45 mg each time, once or twice a week for three to four times) plus Cisplatin (30 to 60 mg/m2) obtained a significant improvement in clinical response and a reduction of failure and progressive disease. Most results had good robustness and moderate quality. Conclusions: Current evidence suggests that Rh-Endostatin with Cisplatin may be an optimal combination, which may improve the clinical response and reduce the failure and progressive disease with good safety. Rh-Endostatin (30 to 40 mg each time, once or twice a week for three to four times) with DDP (30 to 40 mg/m2) may be an optimal usage for achieving an ideal response.